History of Karakoram Highway (Volume I) : The Indus Valley Road - Khalid, Muhammad Mumtaz Brigadier (Retired) (Rawalpindi Hamza Pervez Printers, 2006)
A history of how the Sappers of the Pakistan Army Corps of Engineers built the Karakoram Highway through the rugged terrain of Pakistan.
Include Pictures, Maps and Index
Keywords: Roads -- Pakistan. -- Roads -- Pakistan -- History